(untitled) (Al-Aasar, 2025)
Shari’ah Audit plays a vital role in ensuring that corporate institutions operate in accordance with Islamic principles. The concept of Shari’ah Audit is derived from the need to maintain compliance with Shari’ah in all aspects of business, including employee management, financial transactions, procurement, and operational procedures. This study focuses on evaluating the Shari’ah compliance of various departments, including Sports and Facility Administration, Security and Safety, Construction, Food, Procurement, and Transport, in selected organizations. The research highlights both the strengths and weaknesses of current practices and provides recommendations to ensure ethical and Shari’ah-compliant management. The study emphasizes the protection of employee rights, the observance of fairness, the avoidance of unjust labor practices, and the promotion of equitable treatment in promotions and compensation. By analyzing the existing policies and procedures, this research aims to strengthen organizational systems in line with Shari’ah principles. Moreover, it identifies how proper implementation of Shari’ah Audit contributes to public trust, internal harmony among employees, and long-term organizational sustainability. Therefore, the study is essential not only for ensuring compliance with Islamic law but also for promoting ethical governance and social responsibility in contemporary institutions.